An automatic model and Gold Standard for translation alignment of Ancient Greek - Yousef, Tariq; Palladino, Chiara; Shamsian, Farnoosh; Ferreira, Anise d'Orange [UNESP]; Reis, Michel Ferreira dos [UNESP]; Mariani, J; Calzolari, N.; Bechet, F.; Blache, P.; Choukri, K.; Cieri, C.; Declerck, T.; et al. (European Language Resources Assoc-elra, 2022)
This paper illustrates a workflow for developing and evaluating automatic translation alignment models for Ancient Greek. We designed an annotation Style Guide and a gold standard for the alignment of Ancient Greek-English and Ancient Greek-Portuguese, measured inter-annotator agreement and used the resulting dataset to evaluate the performance of various translation alignment models. We proposed a fine-tuning strategy that employs unsupervised training with mono- and bilingual texts and supervised training using manually aligned sentences. The results indicate that the fine-tuned model based on XLM-Roberta is superior in performance, and it achieved good results on language pairs that were not part of the training data.
Keywords: Translation Alignment; Gold Standard; Alignment Guidelines; Ancient Greek